The impact of mindfulness based cognitive therapy on anxiety in the indian students - Dhawan, Ashu; Singh, Sandeep (International Journal of Psychosocial Rehabilitation, 2020)
Mindfulness based cognitive therapy (MBCT) helps in treating various psychological issues. During academic years students often report different forms of anxiety. Many therapist and academicians contended that MBCT can have positive effects on anxiety among students. This research examines the impact of MBCT on anxiety in the Indian students. The State-Trait Anxiety Inventory (STAI-2) was used to assess baseline scores. We therefore administered the MBCT in students with severe anxiety (N=25) and compared findings at premid-post intervals. The results show that MBCT helps in reducing anxiety among Indian students.